Strengthening the predictive power of screening for adverse childhood experiences (ACEs) in younger and older children. (September 2020) - Turner, Heather A.; Finkelhor, David; Mitchell, Kimberly J.; Jones, Lisa M.; Henly, Megan
Abstract: Background: There is increasing interest in routine screening for Adverse Childhood Experiences (ACEs) to help identify high-risk children who would benefit from interventions. However, there has not yet been sufficient research concerning which particular set of ACEs would be most predictive as a potential screening tool. Objective: This study compared 40 Adverse Childhood Experiences (ACEs), covering 11 different conceptual domains, in their ability to predict trauma symptoms in childhood. Participants and setting: The current study uses pooled data from three National Surveys of Children's Exposure to Violence (NatSCEV) conducted in 2008, 2011, and 2014. Each survey collected information on children aged one month to 17 years. Methods: Samples were obtained from a mix of random digit dialing and address based sampling methods. Telephone interviews were conducted with children 10 years and older and with caregivers, if the randomly selected child was under age 10. Results and conclusion: A different set of 15 items best predicted trauma symptoms for younger (2−9-year-old) compared to older (10−17-year-old) youth. Some conventional ACEs, like physical and emotional abuse, proved important for both age groups. However, family-related factors were more predictive for younger children, while community and peer violence exposures were more predictive for older children. Our new proposed measures explained substantially more variance in subsequent trauma symptoms than did the original ACE measure (R 2 = .31 vs .18 for 2-9 year olds; R 2 = .43 vs .26 for 10-17 year olds; p < .001 for all) and identified a larger percentage of children with high levels of trauma.